An open reading frame upstream from the nifH gene of Klebsiella pneumoniae. - Shen, S C (1983)
An open reading frame upstream from nifHDK operon of Klebsiella pneumoniae had been described. The orientation of this open reading frame is opposite to that of nifHDK and sequence homology was found between the open reading frame promoter and the promoter of nifHDK operon. A recombinant plasmid carrying the promoter region of the open reading frame fused to the beta-galactosidase gene was constructed. Strains of E.coli were transformed with the plasmid containing this open reading frame promoter-lacZ fusion or co-transformed with it and a plasmid carrying the nifA gene. An appreciable activity of beta-galactosidase was found in strains which received both plasmids, indicating that the promoter of the open reading frame can be activated by the product of nifA gene. Thus, the open reading frame found between nifHDK operon and nifJ behaves just like other nif genes of K.pneumoniae in requiring the product of nifA as the positive effector for expression.